Description of two new species of Roussoella (Roussoellaceae, Pleosporales) associated with bamboo from Sichuan Province, China - Wu, Kai; Tian, Wenhui; Syed, Asad; Elgorban, Abdallah M.; Bahkali, Ali H.; Maharachchikumbura, Sajeewa S. N. (Phytotaxa, 2023)
The type genus of the Roussoellaceae family, Roussoella, is mainly known from monocotyledons, particularly on dead bamboo culms, mainly as a saprophyte. This study describes and illustrates two novel species of Roussoella viz. R. fusispora and R. sichuanensis associated with bamboo, collected from Sichuan Province, China. They were identified as new species based on morphology and phylogenetic analyses of a combined matrix of ITS, LSU, TEF1 and RPB2 gene regions. According to multi-gene phylogenetic analysis, R. sichuanensis represents a sister clade to R. multiloculata and R. verrucispora, whereas R. fusispora forms a sister clade to R. neopustulans. Roussoella fusispora exhibits distinct characteristics that differentiate it from R. neopustulans, specifically its relatively smaller asci and ascospores. Similarly, Roussoella sichuanensis can be distinguished from other closely related species primarily based on its comparatively smaller conidia and the presence of a white central ostiole opening on the conidiomata.